Design and Development of An Educational Game for Organic and Inorganic Waste Segregation for Children Aged 5 to 9 Years - Hairu, Syarif; Hidayati, Awanis; Harianto, Nurman (Universitas Pendidikan Indonesia (UPI), 2024)
Waste segregation is a crucial practice for maintaining environmental sustainability. Educating children about the importance of separating organic and inorganic waste from a young age can foster responsible behavior and environmental awareness. This study aims to design and develop an educational game tailored for children aged 5 to 9 years, focusing on teaching them the principles of waste segregation. The research employs a research and development (RD) approach, which includes stages such as needs analysis, game design, development, testing, and evaluation. The game integrates interactive elements, quizzes, and mini-games to engage children while delivering educational content about organic and inorganic waste. A rewards system is incorporated to motivate children to complete levels and reinforce learning.The study's sample consists of 50 children within the specified age range, selected using purposive sampling. Data collection techniques include literature studies, interviews with educators and environmental experts, questionnaires, and observations. Pre-test and post-test assessments are conducted to measure the effectiveness of the game in enhancing children's knowledge about waste segregation.